Achieve culture change to implement your strategic plan. Issue 4 (20th November 2017) - Hope, Joan
Abstract : WASHINGTON, D.C. — When officials at the University of Central Florida set out to create and implement their strategic plan, they wanted to leverage a quality that makes UCF distinctive: it's size. With 64, 000 students, the institution offers that opportunity to "use the power of scale, " as the impact statement for the plan states. But at such a large institution, making sure faculty and staff members across campus understand the plan and their part in it can be a challenge.